High reactivity of nitric oxide with peroxo groups on BaO particles. DFT calculations - Zubieta, Carolina Edith (2013)
The reactivity of the NO molecule with peroxo groups (O2/2-) present on Ba6O6 particles are studied using the density functional theory (DFT). Bulk-like and hexagonal structures were considered. The surface peroxo groups were modeled by adding an oxygen atom (Oa) to a structural oxygen anion (Os). Calculations indicate that the NO molecule can extract either oxygen atom of the peroxo species to form NO2 by surpassing an activation barrier of only 0.2 eV or less. In particular, the NO2 formation via the extraction of Os involves a transition state in which an interchange is produced between Oa and Os. The predicted high reactivity is in agreement with experiments performed on defect-rich BaO wherein NO activation is observed to occur on surface peroxo groups.